MODEL HIDROLIKA UNTUK SIMULASI PROFIL MUKA AIR BANJIR PADA KANAL JONGAYA DALAM PENANGANAN GENANGAN DI KOTA MAKASSAR - Aksan Djamal; Dasyri Pasmar , (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The current condition of the Jongaya Canal outlet has changed significantly. In the outlet area of the Jongaya Canal is a plan for the Makassar Centre Point Of Indonesia (CPI) Area, where this area is a reclamation area. A more in-depth study is needed regarding the change in the use of reclaimed land. So that puddles can be minimized. This study aims to (1) Calculate the reservoir capacity of the Jonaya Canal, (2) Analyze the flood water level with a certain repeat period. The target to be achieved in this study is that the Jongaya Canal is expected to be able to reduce flood peaks in order to reduce the occurrence of floods that often occur in river sections downstream. This research method is research and development by conducting data analysis and evaluation of Canal reservoirs. The analysis review refers to SNI 03-2415-1991 concerning Flood Discharge Calculation Method and SNI 03-2830-1992 concerning Water Level Calculation Method. The results of the study found that the capacity of the Jongaya Canal was 53.54 m3 / s, the catchment area was 12.26 km2 with a channel width that varied from 7 m - 24 m. Variations in the height of the flood face between 1m - 1.5 m were obtained.